Improving ambulatory blood pressure monitoring knowledge in nurses and doctors: impact of a training intervention. (1st December 2018) - Dalfó-Pibernat, Artur; Dalfó Baqué, Antoni; Pelegrina Rodríguez, Francisco Javier; Garin, Olatz; Duran, Xavier; Cladellas Capdevila, Mercè; Comin Colet, Josep
Abstract: Introduction: Ambulatory blood pressure monitoring (ABPM) is fundamental to diagnosing and monitoring arterial hypertension (HTN), yet it is not known how effective training could be in improving knowledge of ABPM. Purpose: The purpose of this study was to evaluate ABPM knowledge before and after a training activity. Methodology: A before-and-after intervention study of 116 professionals. Data was collected on age, sex, occupational category, work setting, and work experience. ABPM knowledge was determined by a questionnaire to evaluate expertise in understanding and interpreting ABPM results. Results: Multivariate regression analysis showed that, pre-intervention, having more than 20 years' experience (odds ratio (OR): 5.9; 95% confidence interval (CI): 1.3–33.9; p = 0.049) and being a doctor (OR: 5.7; 95% CI: 1.8–18.3; p = 0.004) were associated with greater ABPM knowledge. Training increased the number of professionals with adequate ABPM knowledge: 85.3% after training vs 26.7% before training. Training increased the questionnaire mean (SD) score by almost 3 (1.7) points: 9 (2.2) after training vs 6.3 (2.2) before training ( p < 0.05). Of the 116 professionals, 90.5% achieved a higher overall score after training. The impact of the intervention was greatest on women nurses older than 45 years and with more years of experience, employed in primary care, and with prior experience of ABPM. Conclusions: Knowledge of ABPM is deficient but can be easily improved by training that is most effective in primary care and among nurses.